PANDANGAN KIYAI TENTANG PENINGKATAN MUTU KAJIAN KITAB KUNING DI PESANTREN - Nunu Ahmad An-Nahidl (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
Survey of opinion of kiyai on the improvement of quality of study of Kitab Kuning in Pesantren was done in 2014 aimed at finding data and information on expectation of kiyais on aspects of input, process and output of study of kitab kuning in pesantrens. Data was obtained from 22 provinces with 711 kiyais as the samples with systematical random technique. The survey showed that most kiyais give high responses on the indikators used to measure variables of input, process and output. It means that the survey is a factual testimony that most kiyais have positive opinion on the improvement of quality of study of Kitab Kuning in Pesantren